Histological and immunohistochemical comparison of two different allogeneic bone grafting materials for alveolar ridge reconstruction: A prospective randomized trial in humans - Solakoglu, Önder; Götz, Werner; Heydecke, Guido; Schwarzenbach, Heidi (Clinical implant dentistry and related research, 2019)
ABSTRACT Background Preclinical studies have hypothesized a possible immunological reponse to allogeneic materials due to detection of remnants of potential immunogenic molecules. However, their impact on integration, bone remodeling and immunological reaction after the augmentation procedure is largely unknown and a direct correlation of analytical data and evaluation of human biopsies is missing. Purpose The present study aimed to compare two commercially available allogeneic materials regarding their content of cellular remnants as well as the bone remodeling, and integration and potential immunologic reactions on a histological and immunohistochemical level, integrating also in vitro analytical evaluation of the specific batches that were used clinically. Materials and Methods Twenty patients were randomly assigned to treatment with Maxgraft or Puros for lateral ridge augmentation in a two‐stage surgery. After a mean healing period of 5 months, implants were placed and biopsies were taken for histological, immunhistochemical, and histomorphometrical evaluation regarding bone remodeling and inflammation, protein concentrations in vitro and the presence of MHC molecules of the same batches used clinically. Results No differences in clinical outcome, histological, immunohistochemical, and in vitro protein analysis between the two bone grafting materials were observed. Active bone remodeling, amount of newly formed bone, and residual grafting material was independent of the materials used, but varied between subjects. MHC1 residues were not detected in any sample. Conclusions Within the limitations of this study, both tested materials yielded equivalent results in terms of clinical outcome, new bone formation, and lack of immunological potential on a histological and immunohistochemical level.